Java SE 7 programming essentials - Ernest, Michael (Serious skills., 2013)
Full-color guide gives a solid foundation in the fundamentals of Java SE 7 . Also prepares you for the Oracle: OCA: Java SE 7 Programmer certification exam (1Z0-803), covering all topics you need to know for exam.